Pengaruh Reformasi Administrasi Perpajakan Dan Pengetahuan Perpajakan Terhadap Tingkat Kepatuhan Wajib Pajak Pada Kantor Pajak Pratama Pratama Pekanbaru Senapelan Tahun 2018-2020 - Dini Rahmasari; Khairur Raziqin (Institut Ilmu Sosial dan Manajemen STIAMI, 2021)
This study aims to empirically examine the effect of tax administration reform and Tax knowledge on taxpayer compiliance levels at the Primary Tax Office of Senapelan, Pekanbaru in 2018-2020. The research method used was quantitative method with a descriptive approach. Sampling was carried out using Slovin’s theory with a margin of error of 5%, resulting in a sample of 396 respondents. The results of this study indicate that that tax administration reform has a positive and significant effect on taxpayer compliance at the Primary Tax Office of Senapelan, Pekanbaru with a value of 53.7%, and tax knowledge has a positive and significant effect on taxpayer compliance at the Primary Tax Office of Senapelan, Pekanbaru with a value of 49.3%. Simulatneously, tax administration reforms and tax knowledge have a positive and significant effect on tax payer compliance at the Primary Tax Office of Senapelan, Pekanbaru with a value of 60.9%